Clues to the Origins of the Latin Language: An Epigraphic and Cultural Approach - Meledandri, Giovanni; Orsag, Mark (Advances in Social Sciences Research Journal, 2025)
This study hypothesizes, from a philological point of view, the early existence of expressive and communicative skills in the Proto-Latin language of the early Italic peoples based on an engraving found on the 7th century BCE Praeneste fibula. This famed ancient artifact has an extensive, complex and disputed modern history, but its ancient authenticity has now been scientifically confirmed. The goldsmith, (Manios) who made the engraving was likely Etruscan. The inscription thus constitutes compelling evidence that both the carver and the object's patron (Numazios) shared a language, now considered Proto-Latin, that was unambiguously understood by contemporaries. Such a scenario, interestingly, precedes the introduction of Greek philosophical texts concerning the origins and meaning of language to the Italian peninsula by about two centuries.